Auditory Arguments: The Logic of 'Sound' Arguments - Groarke, Leo (Informal Logic)

(untitled) (Informal Logic, 2018)
This article discusses “auditory” arguments: arguments in which non-verbal sounds play a central role. It provides examples and explores the use of sounds in argument and argumentation. It argues that auditory arguments are not reducible to verbal arguments but have a similar structure and can be evaluated by extending standard informal logic accounts of good argument. I conclude that an understanding of auditory elements of argument can usefully expand the scope of informal logic and argumentation theory.